Pengaruh Informasi, Kompetensi, Daya Tanggap dan Akses Terhadap Kepuasaan Pelayanan Wajib Pajak Kendaraan Bermotor Pada SAMSAT Keliling di Kabupaten Banjarnegara - Ratna Suryani; Pandu Pangesty Aji (Medikonis, 2019)
ABSTRACT The purpose of this study is to analyze the influence of information, competence, responsiveness and access to satisfaction of motor vehicle taxpayers services. The samples used in this study were motor vehicle taxpayers in the SAMSAT Mobile service in Banjarnegara Regency. The method used in this sampling is to use the Slovin formula, the data analysis method used is multiple linear regression analysis, using the help of the SPSS program. The results of the testing of the hypothesis indicate that the information variable (X1) has a significant positive effect on taxpayer service satisfaction. Competency variable (X2) has a significant positive effect on taxpayer service satisfaction. The responsiveness variable (X3) has a significant positive effect on satisfaction of taxpayer service satisfaction. Access variable (X4) has a significant positive effect on satisfaction of taxpayer service satisfaction. Based on the results of calculations, of the four variables that provide the greatest influence on satisfaction satisfaction of taxpayer services are competency variables with beta values ​​0,878 and t count 6,316. The results of the coefficient of determination (0.613) indicate that the ability of the independent variables (information, competence, responsiveness and access) in explaining the dependent variable (taxpayer service satisfaction) is very limited and there are still other variables not included in this study.